(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2017)
The historical review of the Venezuelan Actional Art, based on the critical view of Merysol León, is an analytical and reflective contribution for the continuity and deepening of the topic presented. Beyond the simple narration of artistic facts, there is the necessity of advancing and theorizing about the constituent elements of the proposals of artists and artistic collectives. The body, as an artistic object, is essential to communicate through gestures and conventions, an original approach from the interaction of groups of like –minded people, or not. The space, a second element that covers the previous one; and it is available in its proposal. About these two others: time and future, imposes, builds and deconstructs. The convergence of these elements in the step forward of daily life, are the interest of research on the actional art, he development of critical positions and the values approaches of artistic actions.